Changes in activation energy and kinetics of heat-activated persulfate oxidation of phenol in response to changes in pH and temperature. (December 2017) - Ma, Jie; Li, Haiyan; Chi, Liping; Chen, Hongkun; Chen, Changzhao
Abstract: Persulfate (peroxydisulfate, S2 O8 2− ) is the newest oxidant used for the in situ chemical oxidation (ISCO) remediation of soil and groundwater. The present study investigated impacts of solution pH, temperature, and persulfate concentration on the reaction rate constant ( k 1 ), activation energy ( E a ), and reaction order of the heat-activated persulfate process. Phenol was chosen as the model organic contaminant. As temperature increased from 30 °C to 70 °C, k 1 exhibited a significant increase from 0.003 h −1 ∼0.962 h −1 (pH 1.3–13.9) to 1.184 h −1 ∼9.91 h −1 (pH 1.3–13.9), which corroborated with the activation of persulfate using heat. As pH increased from 1.3 to 13.9, k 1 exhibited a 4.3-fold increase at 70 °C and a 320-fold increase at 30 °C, thereby suggesting that: 1) the phenol oxidation rate increased under alkaline conditions, and 2) the enhancement of reaction rate due to alkaline activation was more pronounced at a lower temperature. Increasing pH significantly reduced E a from 139.7 ± 1.3 kJ/mol at pH 1.3 to 52.0 ± 3.3 kJ/mol at pH 13.9. In contrast to changing pH, increasing persulfate concentration from 20 to 320 mM significantly increased k 1 but did not affect E a . Changes in E a suggest that persulfate oxidation of phenol experienced different reaction pathways or elementary reaction sequences as the pH changed from 1.3 to 13.9. In addition, the k 1 and E a data also suggest that a minimal pH threshold of ∼11 was required for the effective alkaline activation of persulfate. Highlights: High temperature activated persulfate and increased the reaction rate ( k 1 ). High solution pH increased k 1 and reduced the reaction activation energy ( E a ). High persulfate concentration increased k 1 but did not changed E a . pH of 10–11 was the lower pH threshold for effective alkaline-activated persulfate.